Impact of exclusive e-cigarettes and heated tobacco products use on muco-ciliary clearance. (August 2021) - Polosa, R.; Emma, R.; Cibella, F.; Caruso, M.; Conte, G.; Benfatto, F.; Ferlito, S.; Gulino, A.; Malerba, M.; Caponnetto, P.
Background: Tobacco smoking impairs mucociliary clearance (MCC) efficiency as shown by prolonged saccharin test transit time (STTT). Avoiding exposure to tobacco smoke from combustible cigarettes may restore MCC function and former smokers have been shown to exhibit similar STTT as never smokers. The impact on STTT of switching from smoking to combustion-free tobacco products such as e-cigarettes (ECs) and heated tobacco products (HTPs) is not known. Methods: We report STTT of exclusive EC and HTP users. Test results were compared with those obtained in current, former, and never smokers. Results: STTT were obtained from 39 current, 40 former, 40 never smokers, and from 20 EC and 20 HTP users. Comparison of STTT values showed significant difference among the five study groups ( p  < 0.00001) with current smokers having a median [interquartile range (IQR)] STTT of 13.15 min, which was significantly longer compared with that of all other study groups. In particular, compared with former (7.26 min) and never smokers (7.24 min), exclusive EC users and exclusive HTP users had similar STTT at 7.00 and 8.00 min, respectively. Conclusion: Former smokers who have switched to exclusive regular use of combustion-free nicotine delivery systems (i.e., ECs and HTPs) exhibit similar saccharin transit time as never and former smokers. This suggests that combustion-free nicotine delivery technologies are unlikely to have detrimental effects on MCC function.